Following psychometric procedures: the development and validation prison distress scale (PDS) (2017)
This study adopted qualitative and quantitative methods to develop and validate Prison Distress Scale as a tool for detecting onset of mental illnesses among convicted prison inmates. The study was conducted in two phases. During the first phase, the initial 51 items were generated through Focus Croup Discussion CFGD) using 24 convicted inmates and Fey Informant Interview (KlI) using 5 convicted. They were purposively sampled from Agodi Prison. Two clinical psychologists and 1 rehabilitation psychologist validated the FCD and Kll Guides. During the second phase, 5 clinical psychologists validated the initial 51 items leaving a total of 47 items. They were administered to 220 convicted inmates were purposively selected from Oyo and Ogbomoso prisons. Their responses were subjected to statistical analysis using SPSS Version 17 and 15 items were found reliable with Cronbach’s Alpha coefficient of 0.84, Spearman Brown Co-efficient of 0.89, and Guttman Split-half Reliability of 0.85. Alpha for the splitted items (A= 0.91 and B = 0,85) were reliable.. The scale was further analyzed using exploratory factor - analysis and van max rotation to address the dimensionality of the scale. The Bartlett Test, Measure of Sampling Adequacy (MSA), and Bartlett Test of Sphericity indicated that the correlation matrix had significant correlations can be factorized. Kaiser-Meyer measure of MSA and Exploratory Factor Analysis yielded five factors explaining a total of 65.26% of the total variance (FMO (91) = 1575.94) and factor loading for the items ranged from 0.58 to 0.78. Factors yielded include Frustration (r= 0.76), Mental Distress (r = 0.70), Loss of Freedom (r = 0.74), and Socio- Emotional., Deprivation A r= 0.62). They formed the sub-scales in the instrument. For the external convergence validity, overall distress was correlated with the Spielbergers State Anxiety Scale and the result demonstrated a strong convergent .validity (r = 0.42, p<.05).The cross validation of Prison Distress Questionnaire with Davidson Trauma Scale yielded low discriminant coefficient of -.52. With this, Nigeria now has a psychological instrument to measure distress among prison inmates